Application Of Psycholinguistics Theories In English Language Classroom: A Review (Journal of Namibian Studies : History Politics Culture, 2023)
To enhance the acquisition of a second language, it is important to develop the four language skills, which include listening, reading, speaking, and writing. The psycholinguistic approach plays a significant role in this process, viewing learning as an individual cognitive process which then moves to the social dimension. Several factors, such as anxiety, intelligence, aptitude, learning styles, personality, motivation, cultural identity, and age, may affect cognitive development. Positive development in these factors can help enhance the acquisition of a second language. Various theories related to individual cognitive development can aid in improving the acquisition of a second language, including Chomsky’s innate theory, B.F. Skinner’s behavioral theory, Jean Piaget’s cognitive theory, and Vygotsky’s sociocultural theory. Methodological tools, such as LCD projectors, group discussion, peer work, Pads, laboratory, note cards, and flashcards, provide a way to develop cognitive processes through classroom activities.